PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia pada Tahun 2014-2017) - Rissa Himmalia, 14.05.52.0192; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2019)
The purpose of this research was to examines the effect and analyze of Firm Size, Profitability, and Business Risk to Capital Structure on manufacturing companies listed on the Indonesia Stock Exchange for period 2014-2017. This research was quantitative and the data type includes time series data. The sample of this research used purposive sampling method. Based on certain criteria, there were 57 companies that matched with the sample. The statistical method used in this research was multiple regression. Based on result from data analysis, Firm Size has the positive effect and significant to Capital Structure with t value 2,037 and significant value 0,046. Profitability has the negative effect and significant to Capital Structure with t value -3,584 and significant value 0,001. Whereas Business Risk has positive effect and not significant to Capital Structure with t value amount 2,494 and significant value 0,015.